Tuberculosis Elimination: Implications and Challenges - Rasha Aziz Salama; Nihal Amir Rizk (Medsci Publications, 2023)
Background: Tuberculosis elimination remains a significant global health challenge, despite the efforts made by governments and international organizations to control and eliminate the disease. The study objectives were to explore the global TB control efforts and highlight the possible challenges and implications in the way to TB elimination. Recommendations to add momentum to current health care efforts were also outlined. Methods: Relevant works of literature were retrieved from different journals and web pages. The electronic databases were searched using the key. Results: A review of the progress made over the past years in the control of TB has shown that the goal of TB elimination has not yet been achieved. The high burden of TB, limited access to TB diagnosis and treatment, drug-resistant TB, weak health systems particularly in low- and middle-income countries, socioeconomic factors, and lack of political commitment and resources are among the major challenges that have hindered the successful elimination of tuberculosis. Conclusions: a sustained and coordinated effort from governments, private sector, international organizations, and other stakeholders, including increased funding, political commitment, and a focus on addressing the root causes of TB transmission and disease burden are required to address these challenges.